Expanding the taxonomic and environmental extent of an underexplored carbon metabolism—oxalotrophy - Sonke, Alexander; Trembath-Reichert, Elizabeth (Frontiers in Microbiology, 2023)
Oxalate serves various functions in the biological processes of plants, fungi, bacteria, and animals. It occurs naturally in the minerals weddellite and whewellite (calcium oxalates) or as oxalic acid. The environmental accumulation of oxalate is disproportionately low compared to the prevalence of highly productive oxalogens, namely plants. It is hypothesized that oxalotrophic microbes limit oxalate accumulation by degrading oxalate minerals to carbonates via an under-explored biogeochemical cycle known as the oxalate-carbonate pathway (OCP). Neither the diversity nor the ecology of oxalotrophic bacteria is fully understood. This research investigated the phylogenetic relationships of the bacterial genes oxc, frc, oxdC, and oxlT, which encode key enzymes for oxalotrophy, using bioinformatic approaches and publicly available omics datasets. Phylogenetic trees of oxc and oxdC genes demonstrated grouping by both source environment and taxonomy. All four trees included genes from metagenome-assembled genomes (MAGs) that contained novel lineages and environments for oxalotrophs. In particular, sequences of each gene were recovered from marine environments. These results were supported with marine transcriptome sequences and description of key amino acid residue conservation. Additionally, we investigated the theoretical energy yield from oxalotrophy across marine-relevant pressure and temperature conditions and found similar standard state Gibbs free energy to “low energy” marine sediment metabolisms, such as anaerobic oxidation of methane coupled to sulfate reduction. These findings suggest further need to understand the role of bacterial oxalotrophy in the OCP, particularly in marine environments, and its contribution to global carbon cycling.